(untitled) (Superficies y Vacío, 2019)
Organic nanoparticles of bifenthrin (agricultural insecticide) were successfully synthesized by the laser ablation of solids in liquids (LASL) technique, using as liquid medium a solution of a polymeric surfactant at 0.1 %. The results showed that the use of the surfactant improves the stability of the organic nanoparticles 18 times as compared to those synthesized in water. The characterization by UV-Vis spectroscopy allowed evaluating the stability of colloids, as well as determining the concentration of nanoparticles in the medium. In the characterization by TEM and HRTEM was possible to observe nanoparticles with the most probable size of 5 nm and interplanar distances which correspond to the crystalline structure of the starting material. Mass coupled gas chromatography technique was used to corroborate the chemical composition of nanoparticles. Results of biological tests using Drosophila Melanogaster fly, showed that the use of the nanostructured compound is effective in lower doses than those used in agriculture in the form of bulk material.